Reduction of antinutrients and maintenance of bioactive compounds in flour from agro-industrial residue of acerola (Malpighia emarginata D.C.) - Barros, Viviane Martins (2020)
This study was aimed at analyzing the reduction of antinutrients, preserving apparent phenolic compounds in acerola flour residue by employing drying techniques. The optimal drying conditions were then determined in the wet residue, analyzing antinutrient concentration and apparent phenolic compounds in the residue and subsequently in the acerola flour. The physicochemical characterization of the flour was carried out, determining its antioxidant activity, thereby assessing the impact of the drying process on the composition of volatile compounds. The optimal drying conditions were found for a temperature of 65ºC for 120 min, reducing water activity by 0.3 and moisture content by 13.89%, which are considered adequate conditions for flours. Carbohydrate content represented 68.72 g/100g, while proteins represented 12.55 g/100g of the centesimal composition of the flour. Significant reductions (p<0.5) of antinutrients were observed in saponins (35.9%), followed by phytates (32.8%) and condensed tannins (11.52%). Losses of 18.7% of apparent phenolic compounds were also observed. For volatile compounds, a significant loss of esters with a significant increase in alcohol content was noticed. Thermal processing reduced aroma complexity, but maintained important bioactive compounds, such as linalool and caryophyllene. In this regard, taking into account the results of the present study, the agro-industrial residue of acerola proved to be an alternative source of antioxidants with a reduced antinutritional impact and may be incorporated as an ingredient in the formulation of new food products. Moreover, this agro-industrial residue reduces the environmental impact caused by the fruit pulp processing industry.